Clinicians’ Guide to the Use of Fecal Calprotectin to Identify and Monitor Disease Activity in Inflammatory Bowel Disease - Brian Bressler; Remo Panaccione; Richard N Fedorak; Ernest G Seidman (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Objective monitoring of the severity of inflammation in patients with inflammatory bowel disease (IBD) is an essential part of disease management. However, repeat endoscopy to define extent and severity of inflammation is not practical. Fecal calprotectin (FC) is a biomarker that can be used as a surrogate test to distinguish inflammatory from noninflammatory gastrointestinal disease.